2004
DOI: 10.1097/01.ccm.0000132898.27101.6c
|View full text |Cite
|
Sign up to set email alerts
|

A potential role of hyperbaric oxygen exposure through intestinal nuclear factor-κB

Abstract: HBOT performed 3 hrs after lipopolysaccharide challenge alleviates intestinal barrier dysfunction and improves survival rates. Herein, we propose one possible mechanism for these beneficial effects: HBOT can modify the nuclear factor-kappaB activation in the intestinal mucosa and attenuate the sequential nitric oxide overproduction and myeloperoxidase activation. Consequently, bacterial translocation could be potentially decreased. We believe that the present study should lead to an improved understanding of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 31 publications
0
30
1
3
Order By: Relevance
“…31 Moreover, HBO treatment was found to decrease nitric oxide production through inhibiting inducible isoform of nitric oxide synthase (iNOS) activation, chemokine production, and leukocyte infiltration by nuclear factor kB (NF-kB)-mediated mechanisms, and to reduce the increase in intestinal permeability and bacterial translocation in a model of intraperitoneal endotoxemia. 32 Our group has also reported decreased bacterial translocation rates in ANP-induced rats after the administration of an iNOS inhibitor. 33 Therefore, the decreased rates of microorganism translocation in our study could possibly have occurred due to a direct inhibitory effect of HBO treatment on intestinal permeability or hematogenous/ lymphatic spread.…”
Section: Discussionmentioning
confidence: 81%
“…31 Moreover, HBO treatment was found to decrease nitric oxide production through inhibiting inducible isoform of nitric oxide synthase (iNOS) activation, chemokine production, and leukocyte infiltration by nuclear factor kB (NF-kB)-mediated mechanisms, and to reduce the increase in intestinal permeability and bacterial translocation in a model of intraperitoneal endotoxemia. 32 Our group has also reported decreased bacterial translocation rates in ANP-induced rats after the administration of an iNOS inhibitor. 33 Therefore, the decreased rates of microorganism translocation in our study could possibly have occurred due to a direct inhibitory effect of HBO treatment on intestinal permeability or hematogenous/ lymphatic spread.…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, HBOT performed 3 h after lipopolysaccharide challenge also alleviated intestinal barrier dysfunction and improved survival rates. As a possible mechanism for these beneficial effects, we found that early HBOT can influence nuclear factor-kappa B activation in the intestinal mucosa and consequently attenuate nitric oxide overproduction and myeloperoxidase activation [22]. Subsequently, we established that this therapy can be safely employed even immediately after surgery, with the same beneficial responses.…”
Section: Introductionmentioning
confidence: 85%
“…Given the general association of high partial oxygen pressures with formation of reactive oxygen species (ROS), the use of HBO in treating conditions which present increased ROS production themselves, such as ischemia/reperfusion injury, appears counterintuitive [2]. Thus, HBO seems to interact with molecular components of the cell, e.g., a wide range of cytokines, which are still not defined in detail [3][4][5].…”
Section: Introductionmentioning
confidence: 99%